Occurrence of selected pharmaceuticals in water and sediment of Umgeni River, KwaZulu-Natal, South Africa - Matongo, Solomon; Birungi, Grace; Moodley, Brenda; Ndungu, Patrick (Environmental Science and Pollution Research, 2015)
Selected pharmaceuticals including antibiotics, antipyretics, a stimulant, an antiepileptic and an antipsychotic drug were determined in wastewater, surface water and sediment along the Umgeni River which is the main source of water to Durban City in KwaZulu-Natal, South Africa. Samples were analysed using high-performance liquid chromatography coupled to a mass spectrometer (HPLC-MS/MS) after clean up and pre-concentration by solid phase extraction (SPE). At the wastewater treatment plant outlet, the antipyretic ibuprofen was detected in concentrations up to 12.94 μg/L and 15.96 ng/g in wastewater and bio-solids, respectively. The antipsychotic clozapine was detected in concentrations up to 14.43 μg/L and 18.75 ng/g in wastewater and bio-solids, respectively. Other pharmaceuticals namely sulfamethazine, sulfamethoxazole, erythromycin, metronidazole, trimethoprim, acetaminophen, caffeine and carbamazepine were also detected but in lower concentration compared to clozapine and ibuprofen (<10 μg/L or 10 ng/g). Clozapine and ibuprofen were detected at high concentrations in the surface water and sediment of Umgeni River. The highest concentration of clozapine (78.33 μg/L) was detected at the business park, while that for ibuprofen (62.0 μg/L) was detected at the point where a tributary, Msunduzi, joins Umgeni. Metronidazole was only detected in sediment, and caffeine (2243.52 ng/g) was detected at the highest concentration in the sediment at the blue lagoon sampling site. The antibiotic sulfamethoxazole was also detected in appreciable amounts up to 507.34 ng/g in the sediment at the Msunduzi tributary sampling site. The data collected implies that while insufficiently treated wastewater contributes to surface water contamination, human activities also contribute appreciably to the pharmaceutical loading of River Umgeni.
Keywords: Pharmaceuticals; Surface water; Sediment; Wastewater; Umgeni River